Forced labor of prisoners of war in Bytom during World War II - Lusek, Joanna (City and War, 2021)
During World War II Upper Silesia was to strengthen the German economic potential by maximizing the involvement of industrial infrastructure for the needs of military operations. The strategic location of Bytom in the region was determined by the possibility of a quick transformation of the existing production from socially useful for the needs of the war economy. This plan was implemented in the second half of the 1930s. Upper Silesia, as a center of heavy industry, was to compete with the Ruhr Area in North Rhine-Westphalia. After the outbreak of World War II, Bytom became part of the Katowice poviat. Heavy industry plants located in and around the city (mines, steel mills and steel mills cooperating with them) were subordinated to the Bytom-Północ Mining Authority (Bergamt Beuthen-Nord), the Bytom-Południe Mining Authority (Bergamt Beuthen-Süd) and partially the Gliwice-Północ Mining Authority (Bergamt Gleiwitz-Nord). The German authorities were looking for an effective way to implement the war production. The idea was to minimize investment and use cheap labor. This allowed for the continuity of production under the conditions of hostilities. In 1940, prisoners of concentration camps, civilian forced laborers and prisoners of war held in the stalags of Lamsdorf and Teschen were brought to industrial plants. Over a 2500 thousand working commandos belonged to the stalags, of which 29 were located in the municipal and land poviats of Bytom. Initially, they were British, French and Belgian prisoners of war. From 1942 they were joined by Soviet prisoners of war, and from 1944 by interned Italian soldiers. Difficulties on the eastern front and the need to reduce production in many plants in 1942–1943 caused a change in the production profile. Single plants started to be included in the armament’s companies. In 1943, coal mining in Upper Silesia reached 100 million tons. In Bytom, as a result of over-exploitation of coal deposits directly outside the city, plans for deglomeration and resettlement of residents to the vicinity of Pyskowice appeared. Ultimately, they were not implemented. In January 1945, there were about 9600 thousand prisoners of war in the working commandos in industrial plants in Bytom and the surrounding area. In the death marches, on foot, they then went deeper into the Third Reich. The barracks were empty.